Six-Minute Walk Test in Healthy Nepalese Young Adults Aged 18 to 25 Years: A Cross- Sectional Study - Chaudhary, Shaligram; Koju, Bibek; Joshi, Lok Raj (Journal of Lumbini Medical College, 2020)
Introduction: The six-minute walk test is a simple test used to assess the exercise capacity. Variability is noted in the six-minute walk distance in different populations. Obesity also affects the six-minute walk test results. The aims of the study were to examine the relationship between body mass index and post exercise oxygen saturation and to establish a reference equation for the six-minute walk distance in young adults.Methods: A cross-sectional study was conducted with 106 subjects of age 18-25 years. The participant walked as fast as possible on a flat surface for six minutes. After a six-minute walk test, oxygen saturation and the distance walked were recorded.Results: Body mass index was negatively correlated with oxygen saturation (r=-0.587,p